2021
DOI: 10.3389/frph.2021.667345
|View full text |Cite
|
Sign up to set email alerts
|

Ibero-American Endometriosis Patient Phenome: Demographics, Obstetric-Gynecologic Traits, and Symptomatology

Abstract: Background: An international collaborative study was conducted to determine the demographic and clinical profiles of Hispanic/Latinx endometriosis patients from Latin America and Spain using the Minimal Clinical Questionnaire developed by the World Endometriosis Research Foundation (WERF) Endometriosis Phenome and Biobanking Harmonization Project (EPHect).Methods: This is a cross-sectional study to collect self-reported data on demographics, lifestyle, and endometriosis symptoms of Hispanic/Latinx endometriosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 60 publications
(102 reference statements)
0
7
0
Order By: Relevance
“…A plausible explanation could be differences in the study design as one study tested a shorter version (EPQ-M) which expectantly led to a faster time-to-complete [36 ± 10.8 min ( 20 )], and another study tested the questionnaire without supervision [30–60 min ( 19 )]. Assuming answering under supervision encourages the participants to keep focus and not to cut corners, we would expect our design and method to result in an increased time-to-complete, as observed ( 22 ).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…A plausible explanation could be differences in the study design as one study tested a shorter version (EPQ-M) which expectantly led to a faster time-to-complete [36 ± 10.8 min ( 20 )], and another study tested the questionnaire without supervision [30–60 min ( 19 )]. Assuming answering under supervision encourages the participants to keep focus and not to cut corners, we would expect our design and method to result in an increased time-to-complete, as observed ( 22 ).…”
Section: Discussionmentioning
confidence: 87%
“…All studies that published comments evaluating the questionnaire reported it being long and/or repetitive ( 19 , 20 , 22 ). Despite these comments, we recommend that investigators use the full questionnaire to ensure the possibility of future collaborations with other research institutions.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, across many different types of pain experienced by patients, Black and Brown patients are often undertreated and underdiagnosed in comparison with non‐Hispanic white patients 195,197 . Hispanic patients who have endometriosis have identified that their dysmenorrhea and high pain are particularly severe, and negatively impact their quality of life 198 . Therefore, these implicit biases that providers impart to their patients and junior‐level trainees have detrimental impacts on patient care.…”
Section: Methodsmentioning
confidence: 99%
“…195,197 Hispanic patients who have endometriosis have identified that their dysmenorrhea and high pain are particularly severe, and negatively impact their quality of life. 198 Therefore, these implicit biases that providers impart to their patients and junior-level trainees have detrimental impacts on patient care. Thus, it is particularly important to understand how to address implicit biases in health care as we attempt to understand how to better attend to the needs of marginalized communities affected by endometriosis.…”
Section: Diagnosismentioning
confidence: 99%
“…Current research cohorts do not well reflect the clinical population in which they are hoping to have impact. We are aware of new cohorts being set up in under-researched regions [48][49][50][51][52][53], but it is increasingly clear that there are systemic disparities in access to care throughout the developed world [54]. Thus, continuing to focus our research efforts only on those with a surgical diagnosis will perpetuate these biases.…”
Section: Future Workmentioning
confidence: 99%